Developing Ethnopedagogical Interactive Media to Improve Fifth-Grade Students’ Social Studies Concept Understanding - Sriati Sriati; Ismira Ismira; Hafiz Hidayat (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2026)
This study aimed to develop ethnopedagogical-based interactive learning media to improve fifth-grade elementary school students’ conceptual understanding in Social Studies learning. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The effectiveness of the developed media was examined using a quasi-experimental pretest–posttest control group design involving 50 fifth-grade students from two elementary schools in Kerinci Regency, Indonesia. Data were collected through expert validation sheets, conceptual understanding tests, and student response questionnaires. The developed media integrated Kerinci local cultural values into interactive digital learning materials through multimedia features such as images, videos, animations, and quizzes. The validation results showed that the media achieved an average score of 93.7%, indicating a highly valid category. The practicality test results showed a percentage score of 88.13%, categorized as highly practical. The effectiveness analysis revealed a significant improvement in students’ conceptual understanding, indicated by an increase in the average score from 55.275 in the pretest to 80.335 in the posttest. The N-Gain result of 0.561 was categorized as moderate improvement, while the Independent Sample t-test showed a significant difference between the experimental and control groups (p < 0.05). These findings indicate that ethnopedagogical-based interactive learning media is valid, practical, and effective in improving students’ conceptual understanding in Social Studies learning. The integration of local cultural values into digital learning media also contributes to more contextual and meaningful learning experiences in elementary schools.